Plant‐expressed Fc‐fusion protein tetravalent dengue vaccine with inherent adjuvant properties. Issue 7 (1st February 2018) - Kim, Mi Young; Copland, Alastair; Nayak, Kaustuv; Chandele, Anmol; Ahmed, Muhammad S.; Zhang, Qibo; Diogo, Gil R.; Paul, Matthew J.; Hofmann, Sven; Yang, Moon‐Sik; Jang, Yong‐Suk; Ma, Julian K‐C.; et al.
Summary: Dengue is a major global disease requiring improved treatment and prevention strategies. The recently licensed Sanofi Pasteur Dengvaxia vaccine does not protect children under the age of nine, and additional vaccine strategies are thus needed to halt this expanding global epidemic. Here, we employed a molecular engineering approach and plant expression to produce a humanized and highly immunogenic poly‐immunoglobulin G scaffold (PIGS) fused to the consensus dengue envelope protein III domain (cEDIII). The immunogenicity of this IgG Fc receptor‐targeted vaccine candidate was demonstrated in transgenic mice expressing human FcγRI/CD64, by induction of neutralizing antibodies and evidence of cell‐mediated immunity. Furthermore, these molecules were able to prime immune cells from human adenoid/tonsillar tissue ex vivo as evidenced by antigen‐specific CD4 + and CD8 + T‐cell proliferation, IFN‐γ and antibody production. The purified polymeric fraction of dengue PIGS (D‐PIGS) induced stronger immune activation than the monomeric form, suggesting a more efficient interaction with the low‐affinity Fcγ receptors on antigen‐presenting cells. These results show that the plant‐expressed D‐PIGS have the potential for translation towards a safe and easily scalable single antigen‐based tetravalent dengue vaccine.